2014
DOI: 10.1038/pr.2014.192
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotics (Lactobacillus acidophilus and Bifidobacterium bifidum) prevent NEC in VLBW infants fed breast milk but not formula

Abstract: Background: Specific probiotics prevent necrotizing enterocolitis (NEC). A mixture of lactobacilli and bifidobacteria (Infloran) was highly effective in Asian very-low-birth-weight (VLBW) infants. We analyzed the effect of Infloran on NEC, NEC severity, and the influence of enteral feedings (breast milk vs. formula) on NEC prevention in a cohort of European VLBW infants. Methods: Infloran was implemented for routine use at our department. VLBW infants receiving probiotics were prospectively followed (2010)(201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 40 publications
0
69
0
2
Order By: Relevance
“…Eight studies [48,51,52,53,54,58,59,60] reported on late-onset sepsis. The administration of probiotics reduced the incidence of sepsis in VLBW infants by 19% (RR 0.81, 95% CI 0.69-0.96, p = 0.01; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies [48,51,52,53,54,58,59,60] reported on late-onset sepsis. The administration of probiotics reduced the incidence of sepsis in VLBW infants by 19% (RR 0.81, 95% CI 0.69-0.96, p = 0.01; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using the probiotic preparation Infloran (a mixture of L. acidophilus and B. infantis ), 1 RCT trial demonstrated a reduction of NEC and mortality by approximately 80% [32]. Pooled analyses of 4 observational studies [50,51,53,59] showed a statistically significant 51% reduction of NEC and 46% reduction of mortality. Recently, a large observational multicentre study conducted by Denkel et al [71] demonstrated that the routine use of dual-strain probiotics (Infloran) in German neonatal wards significantly reduced the risk of NEC, overall mortality, and late-onset sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies [13,14] had insufficient data presentation (only on preterm neonates) and were therefore not included in the meta-analysis calculation. Hence, 12 studies were pooled in the meta-analysis, including a total of 10,800 neonates [15,16,17,18,19,20,21,22,23,24,25,26]. Details of the selection process are shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies covered a large geographical area. All included studies were longitudinal cohort studies, either retrospective [15,16,19,22,23], prospective [17,18,20,21,24,26] or with a historical control group [25]. Ten of the included studies were single-center studies and 2 were multicenter [17,23].…”
Section: Resultsmentioning
confidence: 99%
“…), the difficulty in accessing safe and clinical proven probiotic products, and the risk of probiotic sepsis. Almost all other issues, including 'We don't know how probiotics work', 'Probiotics are not needed if the infant is fed breastmilk -the nature's synbiotic, or when the baseline incidence of NEC is low', 'The PIPs trial showed that not all probiotic strains are effective, and challenged the previous meta-analyses', 'There is not enough data on extremely low birth weight (ELBW) infants, and probiotics may not have significant benefits in this population', have been addressed over the last few years [3][4][5][6][7]. Probiotic sepsis is easy to treat compared to sepsis by other potentially disastrous (e.g.…”
mentioning
confidence: 99%